Socio-economic development as a determinant of migration transition in Central and Eastern European Countries - Bugowski, Łukasz Karol (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: A concept that links the question of the intensity and direction of migration process with the process of socio-economic transformation is the migration transition theory. The migration transition comprises two phases. In the first phase, there is a significant increase in emigration processes due to the intensely increasing birth rate. In the second phase, on the other hand, an increase in immigration processes is observed, which is preceded or accompanied by a zero or negative natural increase. Currently, a similar change from negative to positive net migration balance can be observed in the countries of Central and Eastern Europe. Aim: The aim of this article is the evaluation of the intensity and directions migration processes in the countries of Central and Eastern Europe. The research question is whether the positive net migration balances achieved by the countries of Central and Eastern Europe can be considered as confirmation that these countries are in the second phase of the migration transition. The research question is validated by analysing statistical data (Eurostat) and the results of the European Social Survey, which is preceded by a review of the literature in question. Results: As a result of the progressive socio-economic development, Central and Eastern Europe is attracting new residents. The scale of this phenomenon is evidenced not only by the number of registered migrations, but above all by the number of first residence permits for work, education and family reasons. Stable economic growth and increasing labour shortages have created ideal conditions for labour immigration in recent years. It can therefore be concluded that the socio-economic development of the macro-region under study has contributed to the second stage of the migration transition, characterised by a positive net migration balance.